Structure, electronic and magnetic properties of Ca-doped chromium oxide studied by the DFT method - Maldonado, F. (2012)
Using first-principles density functional theory calculations within the generalised gradient approximation (GGA) as well as GGAU method we study Ca-doped ?-Cr 2O 3 crystal. Structural, electronic and magnetic properties due to the singular impurity incorporation have been investigated and discussed in detail. Atomic shifts as well as computed Bader charges on atoms imply the importance of ionic nature in the atomic interactions in chromium oxide. The study improves our knowledge on how the crystalline lattice reacts on the presence of a Ca dopant. According to our research it is found that Ca impurity incorporation produces some local changes upon the electronic band structure of the material without occurrence of local states within the band-gap. It is found that Ca incorporation produces change in magnetic behaviour of the crystal: it becomes ferromagnetic. © 2012 Elsevier B.V. All rights reserved.